Leveraging COBIT 2019 to Implement IT Governance in Mineral Mining Company - Ray Farhan Mubarak; Melissa Indah Fianty (Universitas Bina Darma, 2023)
The integration of Information Technology (IT) in companies comes with its own set of challenges. One major issue is the loss of operational data, which directly affects the company's workflow and disrupts its activities. To tackle this problem, the company assesses its IT capability using the COBIT 2019 framework. This framework outlines the objectives of different IT processes and assigns predetermined values to each process. The assessment reveals three levels of IT capability for specific processes within the company: EDM03 (Ensured Risk Optimization) at level 3, APO13 (Managed Security) at level 2, and MEA03 (Managed Compliance with External Requirements) at level 3. The company aims to reach level 4 for these processes. Consequently, recommendations for improvement primarily focus on enhancing the management of information security risks and information security management systems, as well as increasing compliance with policies and regulations.